Adaptation of retinal ganglion cell function during flickering light in the mouse - Chou, Tsung-Han (Sci Rep, 2019)
Rapid dilation of retinal vessels in response to flickering light (functional hyperemia) is a well-known autoregulatory response driven by increased neural activity in the inner retina. Little is known about flicker-induced changes of activity of retinal neurons themselves. We non-invasively investigated flicker-induced changes of retinal ganglion cell (RGC) function in common inbred mouse strains using the pattern electroretinogram (PERG), a sensitive measure of RGC function. Flicker was superimposed on the pattern stimulus at frequencies that did not generate measurable flicker-ERG and alter the PERG response. Transition from flicker at 101 Hz (control) to flicker at 11 Hz (test) at constant mean luminance induced a slow reduction of PERG amplitude to a minimum (39% loss in C57BL/6J mice and 52% loss in DBA/2J mice) 4–5 minutes after 11 Hz flicker onset, followed by a slow recovery to baseline over 20 minutes. Results demonstrate that the magnitude and temporal dynamics of RGC response induced by flicker at 11 Hz can be non-invasively assessed with PERG in the mouse. This allows investigating the functional phenotype of different mouse strains as well as pathological changes in glaucoma and optic nerve disease. The non-contact flicker-PERG method opens the possibility of combined assessment of neural and vascular response dynamics.